Alopecia Areata Incognita and Diffuse Alopecia Areata: Clinical, Trichoscopic, Histopathological, and Therapeutic Features of a 5-Year Study - Aurora Alessandrini (Mattioli1885, 2019)
Background: Alopecia areata is a nonscarring hair loss that usually causes round patches of baldness, but alopecia areata incognita (AAI) and diffuse alopecia areata (DAA) can cause a diffuse and acute pattern of hair loss.